A fixed point approach to stability of functional equations - Brzdȩk, Janusz; Chudziak, Jacek; Páles, Zsolt (Nonlinear analysis, 2011)
We prove a simple fixed point theorem for some (not necessarily linear) operators and derive from it several quite general results on the stability of a very wide class of functional equations in single variable.